Feasibility Research of Luma Prediction Mode Encryption after HEVC Encoding - Tang, Bo; Yang, Cheng (2021 IEEE International Conference on Information Communication and Software Engineering (ICICSE), 2021)
The rapid development of communication and multimedia technology has created the possibility for the production and application of Ultra High Definition (UHD) immersive video, but the content security protection of UHD immersive is threatened. Most of the existing video Selective Encryption (SE) algorithms are completed during the encoding, the highly coupling makes the application difficulties. The SE algorithms after encoding have the advantages of flexibility and efficiency, but the interaction between the syntax elements makes the encryption more restricted. Designing a SE algorithm after encoding with coding format compatibility needs to analyze the encryptability of important syntax elements. One of the main tasks of video content protection is to hide the structural information of image. Luma prediction mode is an important element for reconstructing the image structure during decoding, which can the image structural when it is encrypted. This paper analyzes the encryptable of the syntax elements of the luma prediction mode in High Efficiency Video Coding (HEVC) after video encoding, the result shows that the intra_luma_pred_mode syntax element has two sets of encryptable ranges which can maintain the scanning mode, but the ranges is too small and the prediction modes within range is similar, so encryption of this element does not have sufficient content video content protection capabilities.